CRITICAL RACE THEORY AND INTERSECTIONALITY: AN ANALYSIS - Dr. M. P. RESHMA (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This paper delves into the nuances of the highly controversial Critical Race Theory, and studies the core concept of intersectionality that is embodied within. Founded by Kimberly Crenshaw, Critical Race Theory is at a pivotal point in American history now. With the Trump administration intervening at its every academic, social and political discourses; Critical Race Theory is perceived by the majority of white Americans as a threat to the unity and political correctness of the nation. However, intersectionality remains an infallible process for research and interrogations on the matters of race and gender privileges and discriminations. This paper traces out the origin of the concept of intersectionality and also discusses the functionality of the concept in understanding race and such discriminatory ideologies.